Preparation method of II-type heterojunction photocatalyst, product and application of II-type heterojunction photocatalyst in photocatalytic degradation of levofloxacin

The type II heterojunction photocatalyst g-C3N4/Bi2WO6 (MCN/BWO) synthesized by the hydrothermal method efficiently degrades levofloxacin (LEV) antibiotics in water under photocatalysis, solving the problems of low removal efficiency and poor light stability in the prior art, and achieving efficient and stable LEV degradation effect.

CN119524904AInactive Publication Date: 2025-02-28DALIAN NATIONALITIES UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411707374.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove levofloxacin (LEV) antibiotics in water, and traditional methods have problems such as low removal efficiency and poor light stability.

Method used

Type II heterojunction photocatalyst g-C3N4/Bi2WO6 (MCN/BWO) was synthesized by hydrothermal method, and its efficient degradation ability of LEV under photocatalysis was utilized.

Benefits of technology

The removal efficiency of LEV is achieved up to 98.14%, and it shows excellent light stability and adaptability. It is suitable for efficient removal of difficult-to-degrade organic pollutants in wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524904A_ABST
    Figure CN119524904A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photocatalyst preparation and antibiotic degradation, in particular to a preparation method of an II-type heterojunction photocatalyst, a product and application of the II-type heterojunction photocatalyst in photocatalytic degradation of levofloxacin. The preparation method of the II-type heterojunction photocatalyst comprises the following steps: dissolving g-C3N4 nanosheets and a tungsten source in water, and uniformly mixing to obtain a solution A; dissolving a bismuth source in glacial acetic acid to obtain a solution B; adding the solution B into the solution A to obtain a suspension C; the suspension C is subjected to a hydrothermal reaction, and the II-type heterojunction photocatalyst is obtained. According to the invention, the II-type heterojunction photocatalyst which can be used for degrading levofloxacin (LEV) is synthesized by adopting a one-step hydrothermal method. The removal efficiency of the II type heterojunction photocatalyst on LEV is as high as 98.14%; the II-type heterojunction photocatalyst disclosed by the invention shows excellent light stability and adaptability, and has high-efficiency practicability when being used for removing refractory organic pollutants in wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalyst preparation and antibiotic degradation, and in particular to a preparation method and product of a type II heterojunction photocatalyst and application thereof in photocatalytic degradation of levofloxacin. Background Art

[0002] In recent years, antibiotics have been widely used in human medicine, agriculture, and animal and plant breeding, playing an important role in treating infections in humans and animals. However, over-reliance on antibiotics has led to elevated levels of these compounds in the environment, especially in aquatic environments, which disrupts the balance of bacterial reproduction in existing ecosystems, promotes the emergence of antibiotic resistance, and introduces new physiological risks through bioaccumulation. In addition, natural processes may also cause antibiotics to decompose into more harmful substances. It is estimated that 100,000 to 200,000 tons of antibiotics are used worldwide each year. Its use has increased by more than 65% in the past 20 years and is expected to double by 2030. Fluoroquinolones (FQs) are drugs with broad-spectrum antibacterial ability, which have good therapeutic effects on diseases caused by bacterial infections and are widely used to treat various bacterial infections. Levofloxacin (LEV) is a commonly used fluoroquinolone antibiotic with good antibacterial effects against a variety of bacteria. It is widely used to treat various diseases, including bacterial infections, inflammation, such as respiratory tract, urinary system malformations, intestinal mucosa and skin. However, the widespread use of antibiotics can cause damage to the environment, mainly because this water-soluble drug contaminant can easily enter water bodies through sewage pipes, and the high polarity and non-volatility of the compound increase the difficulty of the separation process.

[0003] Therefore, providing a photocatalyst for LEV to improve the degradation effect of LEV is of great significance to the field of photocatalyst preparation and antibiotic degradation technology. Summary of the invention

[0004] Based on the above content, the present invention provides a preparation method and product of a type II heterojunction photocatalyst and its application in photocatalytic degradation of levofloxacin.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is a method for preparing a type II heterojunction photocatalyst, comprising the following steps:

[0007] The g-C3N4 nanosheets and tungsten source were dissolved in water and mixed to obtain solution A;

[0008] Dissolve the bismuth source in glacial acetic acid to obtain solution B;

[0009] Adding the solution B into the solution A to obtain a suspension C;

[0010] The suspension C is subjected to a hydrothermal reaction to obtain the type II heterojunction photocatalyst (MCN / BWO).

[0011] The second technical solution of the present invention is a type II heterojunction photocatalyst prepared according to the above-mentioned preparation method.

[0012] The third technical solution of the present invention is the use of the above-mentioned type II heterojunction photocatalyst in the photocatalytic degradation of fluoroquinolone drugs.

[0013] The present invention discloses the following technical effects:

[0014] The present invention adopts a one-step hydrothermal method to synthesize a g-C3N4 / Bi2WO6 (MCN / BWO) type II heterojunction photocatalyst that can be used for levofloxacin (LEV) degradation.

[0015] The type II heterojunction photocatalyst prepared by the method of the present invention has a removal efficiency of up to 98.14% for LEV; the type II heterojunction photocatalyst of the present invention exhibits excellent light stability and adaptability, and is highly effective and practical in removing difficult-to-degrade organic pollutants in wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 (a) XRD pattern of MCN / BWO, (b) FT-IR spectrum of MCN / BWO.

[0018] Figure 2 FESEM images of (a) CN, (b) MCN, (c) BWO, (d) MCN / BWO (1:1), (e) MCN / BWO (1:3), (f) MCN / BWO (3:1) and elemental mapping of (g1)-(h) MCN / BWO (1:1) heterojunction photocatalysts, (i)-(k) TEM and HR-TEM images of MCN / BWO (1:1).

[0019] Figure 3 (a) XPS measurement spectrum and high-resolution XPS spectra of (b) C 1s, (c) N 1s, (d) Bi 4f, (e) W4f and (f) O 1s.

[0020] Figure 4(a) UV-vis DRS spectra, (b) (αhν) obtained from MCN and BWO 2 and (αhν) 1 / 2 , (c) Mott-Schottky curve, (d) VB-XPS graph of MCN and BWO, (e) photoluminescence spectrum, (f) EIS graph, (g) it curve, (h) SPV spectrum of MCN / BWO (1:1).

[0021] Figure 5 (a) Photocatalytic degradation curves of LEV by different photocatalysts under simulated sunlight, (b) degradation rate of LEV by MCN / BWO (1:1) under different light intensities, and (c) corresponding pseudo-first-order kinetic curves.

[0022] Figure 6 (a) Cyclic experiment diagram of MCN / BWO (1:1) degradation of 15 mg / L LEV and (b) XRD patterns of MCN / BWO (1:1) photocatalyst before and after the cycle experiment.

[0023] Figure 7 (a) Effects of various scavengers on the photocatalytic degradation of LEV by MCN / BWO (1:1) heterojunction photocatalyst and (b) the corresponding degradation rates; (c) DMPO-·O2 - and (d) ESR spectra of DMPO-·OH through MCN / BWO (1:1) in the dark and under light.

[0024] Figure 8 Three-dimensional excitation-emission matrix fluorescence spectra (3D EEMs) of LEV solutions; (a) was taken from the original solution, (b) was extracted from the solution after adsorption for 30 min, and (c)-(h) were collected after 30, 60, 90, 120, 150, and 180 min of solar light irradiation, respectively.

[0025] Fig. 9 This is the degradation pathway of LEV in the MCN / BWO system.

[0026] Fig.10 Ecotoxicity of LEV and degradation intermediates: (a) Daphnia magna LC 50 (48h); (b) Fathead minnow LC 50 (96h); (c) oral LD ​​in rats 50 ; (d) mutagenicity; (e) developmental toxicity; (f) bioaccumulation factor.

[0027] Fig.11 Schematic diagram of the synthesis process of MCN / BWO photocatalyst.

[0028] Fig.12Schematic diagram of the photocatalytic mechanism of MCN / BWO heterojunction. DETAILED DESCRIPTION

[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0030] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0034] A variety of antibiotic removal methods have been developed in the existing technology, such as biological treatment, membrane treatment, electrochemical methods, ion exchange, adsorption and advanced oxidation processes (AOPs). AOPs provide an effective method for removing antibiotic pollutants from wastewater through highly active free radicals. Due to their broad-spectrum characteristics of high removal efficiency, fast reaction rate and good design adaptability, AOPs have excellent application prospects in the field of water treatment. Photocatalysis is a typical AOPs method. Due to its recyclability, clean solar energy utilization and high performance, it has become a cost-effective and environmentally friendly way to remove organic pollutants. In addition, exploring composite nanomaterials for photocatalytic adsorption and degradation of organic pollutants has become the first choice for AOPs methods.

[0035] Graphitic carbon nitride (g-C3N4) is an emerging non-metallic material. Due to its low cost, narrow band gap (2.7 eV), wide absorption spectrum, high catalytic activity, good thermochemical stability, non-toxicity, lack of precious metals and large specific surface area, g-C3N4 materials have attracted widespread attention in recent years and have been widely used in semiconductors, photocatalysts, catalyst supports and energy storage materials. However, g-C3N4 still has some defects, such as low visible light absorption capacity of g-C3N4, high recombination rate of photogenerated electron-hole pairs, and small specific surface area (SSA). In order to overcome these shortcomings, researchers have tried different modification strategies, such as designing nanostructures (template and template-free synthesis, exfoliation and self-assembly), element doping and constructing heterojunctions. Among these strategies, combining g-C3N4 with other semiconductors to construct heterojunctions is considered to be a simple and effective method. Ternary metal oxide Bi2WO6 is a promising candidate material due to its unique structure, chemical stability, excellent photocatalytic activity, and energy gap of 2.7-2.9 eV (n-type semiconductor), which can be photocatalytically active under visible light. g-C3N4 / Bi2WO6 exhibits excellent photocatalytic performance towards organic dyes, tetracycline, ibuprofen, bisphenol A and ceftriaxone sodium. However, there are few studies on the composite adsorption-photocatalytic degradation of fluoroquinolone antibiotics by g-C3N4 / Bi2WO6. Therefore, the present invention attempts to improve the photocatalytic performance of g-C3N4 by constructing a type II heterojunction and apply it to the removal of fluoroquinolone antibiotics. The present invention comprehensively compares the removal effects of g-C3N4 / Bi2WO6 with different molar ratios on LEV in polluted water. In order to remove LEV from water, a new direct all-solid phase type II g-C3N4 / Bi2WO6 heterojunction composite photocatalytic material was prepared by a simple hydrothermal method, and the prepared photocatalytic material was characterized. The pseudo-first-order kinetic model was used to fit the photocatalytic degradation process. The photocatalytic mechanism was revealed through photoelectrochemical property analysis, free radical quenching experiment and electron spin resonance (ESR) spectroscopy. Finally, under simulated sunlight conditions, the enhanced mechanism of type II g-C3N4 / Bi2WO6 heterojunction material on the removal of LEV in water was explored, and the possible degradation intermediates and degradation pathways of LEV were analyzed by LC-MS. The ecotoxicity of the degradation products was comprehensively evaluated using the toxicity assessment software TEST and the quantitative structure-activity relationship (QSAR) model. This study provides new ideas for further exploring the photocatalytic mechanism of type II heterojunction and removing antibiotics in water environments.

[0036] The first aspect of the present invention provides a method for preparing a type II heterojunction photocatalyst, comprising the following steps:

[0037] The g-C3N4 nanosheets and tungsten source were dissolved in water and mixed to obtain solution A;

[0038] Dissolve the bismuth source in glacial acetic acid to obtain solution B;

[0039] Adding the solution B into the solution A to obtain a suspension C;

[0040] The suspension C is subjected to a hydrothermal reaction to obtain the type II heterojunction photocatalyst (MCN / BWO).

[0041] In a preferred embodiment of the present invention, the g-C3N4 nanosheets are made from melamine.

[0042] In a preferred embodiment of the present invention, the method for preparing the g-C3N4 nanosheets comprises the following steps:

[0043] After the first calcination of melamine, CN is obtained;

[0044] The CN is calcined for a second time to obtain the g-C3N4 nanosheets.

[0045] In a preferred embodiment of the present invention, the temperature of the first calcination is 550-600° C., and the time is 4-5 hours; the temperature of the second calcination is 500-550° C., and the time is 2-3 hours.

[0046] In some specific embodiments of the present invention, the heating rate of the first calcination is 5°C / min; the heating rate of the second calcination is 10°C / min.

[0047] In a preferred embodiment of the present invention, the molar ratio of the g-C3N4 nanosheets to the sodium tungstate and bismuth nitrate is (1-3):1:2; the tungsten source is sodium tungstate; and the bismuth source is bismuth nitrate.

[0048] In a further preferred embodiment of the present invention, the molar ratio of the g-C3N4 nanosheets to the sodium tungstate is 1:1.

[0049] The present invention does not impose any particular limitation on the amount of water and glacial acetic acid used, as long as the amount of water and glacial acetic acid can fully dissolve the raw materials.

[0050] In a preferred embodiment of the present invention, the temperature of the hydrothermal reaction is 160-180° C. and the time is 12-13 hours.

[0051] In a preferred embodiment of the present invention, after the hydrothermal reaction is completed, the steps of collecting the product by centrifugation and washing and drying are also included.

[0052] In some embodiments of the present invention, the drying temperature is 60°C.

[0053] The second aspect of the present invention provides a type II heterojunction photocatalyst prepared according to the above-mentioned preparation method.

[0054] The third aspect of the present invention provides a use of the above-mentioned type II heterojunction photocatalyst in the photocatalytic degradation of fluoroquinolone drugs.

[0055] In a preferred embodiment of the present invention, the fluoroquinolone drug is levofloxacin.

[0056] The removal efficiency of LEV by MCN / BWO (1:1) prepared by the method of the present invention is 98.14%, and the apparent reaction rate constant is about 2.6 times that of MCN, 1.2 times that of BWO, 1.4 times and 2.4 times that of MCN / BWO (1:3) and MCN / BWO (3:1). This enhanced photocatalytic performance is attributed to the effective utilization of visible light and the construction of type II heterojunction. In addition, the band structure was studied by valence band X-ray photoelectron spectroscopy (VB-XPS), Mott-Schottky plot and UV-visible diffuse reflectance (DRS). The photocatalytic reaction mechanism under light irradiation was comprehensively studied by free radical scavenging experiments and electron spin resonance (ESR). The photocurrent response, electrochemical impedance spectroscopy (EIS) and surface photovoltage (SPV) results confirmed the photocatalytic enhancement of the heterojunction. The reusability and performance of this type of heterojunction were studied in 3 cycles, and the material still maintained high degradation performance of 97.48%, 96.96% and 92.58% after 3 cycles. The degradation pathways and ecotoxicity of LEV and its degradation products were elucidated by LC-MS and Toxicity Estimation Software Tool (TEST). Quantitative structure-activity relationship (QSAR) evaluation showed that the ecotoxicity of many intermediates was lower than that of LEV. The MCN / BWO heterojunction exhibited excellent photostability and adaptability, and was highly practical in removing recalcitrant organic pollutants from wastewater.

[0057] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.

[0058] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0059] Example 1

[0060] 1. Materials and methods

[0061] 1.1 Materials

[0062] Melamine (C3H6N6, 99.5%) was provided by Tianjin Guangfu Fine Chemical Research Institute (Tianjin, China). Bismuth nitrate pentahydrate (Bi(NO3)3·5H2O, 99.0%) was purchased from Shanghai Aladdin Reagent Co., Ltd. (Shanghai, China). Sodium tungstate dihydrate (Na2WO4·2H2O), levofloxacin (C 18 H 20 FN3O4) was provided by Sinopharm Chemical Reagent Co., Ltd. (China). Glacial acetic acid (CH3COOH) was purchased from Tianjin Komiou Chemical Reagent Co., Ltd. (Tianjin, China). Ethanol (CH3CH2OH, 99.7%) was purchased from Tianda Chemical Reagent Co., Ltd. (Tianjin, China). Deionized water was used in all experiments unless otherwise stated. In addition, all chemicals used in the present invention were of analytical grade (AR) without further purification.

[0063] 1.2 Preparation of photocatalyst

[0064] 1.2.1 Preparation of MCN nanosheets

[0065] The synthesis of graphitic carbon nitride (g-C3N4) nanosheets involves a direct thermal polycondensation method. Initially, a 50 mL covered ceramic crucible is used, in which 10 g of melamine is placed. Subsequently, the crucible is transferred to the central area of ​​the crucible furnace. The calcination temperature is 550°C, the heating rate is 5°C / min, and the calcination time is 4h. Once the crucible cools to room temperature, the resulting yellow solid product is finely ground into a powder, denoted as CN. In a subsequent step, a ceramic crucible is filled with 1 g of CN powder and loaded into a crucible furnace. The calcination process is carried out at 500°C, the heating rate is 10°C / min, and the calcination duration is 2h. After the ceramic crucible is cooled to room temperature, the yellow product obtained is g-C3N4 nanosheets, denoted as MCN. The prepared bulk MCN is then kept in a dry place.

[0066] 1.2.2 Synthesis of photocatalyst (MCN / BWO)

[0067] MCN / BWO heterojunction composites were prepared by a simple hydrothermal method. 1mmol sodium tungstate (Na2WO4·2H2O) and different millimoles of MCN were dissolved in 60mL deionized water (the amount of MCN added was 1mmol, 1 / 3mmol, and 3mmol, respectively, so that the molar ratio of MCN to sodium tungstate was 1:1, 1:3, and 3:1), and ultrasonic treatment was performed for 30min to obtain solution A. 2mmol bismuth nitrate (Bi(NO3)3·5H2O) was dissolved in 5mL glacial acetic acid to obtain solution B. Solution B was poured dropwise into solution A and stirred to obtain suspension C. Magnetic stirring was continued for 60min, and then suspension C was transferred to a 100mL polytetrafluoroethylene-lined autoclave and placed in an oven. The oven was heated to 160℃ at a rate of 2℃ / min, and the reaction was continued for 12 hours. Finally, the obtained product was collected by centrifugation, washed with deionized water and anhydrous ethanol for 6 times, and then dried at 60℃ to obtain MCN / BWO. Specifically, according to the molar ratio of MCN to sodium tungstate in MCN / BWO of 1:1, 1:3 and 3:1, they are marked as MCN / BWO (1:1), MCN / BWO (1:3), and MCN / BWO (3:1). Pure Bi2WO6 is prepared by the above method without adding MCN, which is represented by BWO (that is, the only difference from the preparation method in 1.2.2 is that the addition of MCN is omitted, and the other steps and parameters are the same as 1.2.2). The formation process is shown in Fig.11 middle.

[0068] 1.3 Characterization

[0069] The crystal structure of the photocatalyst was determined by X-ray diffractometer (XRD, Shimadzu XRD-6000), and the photocatalyst was characterized by Fourier transform infrared spectroscopy (FT-IR, Shimadzu IR Prestige-21) at 400-4000 cm -1The surface functional groups of the photocatalyst were analyzed within a range of 100 nm. The morphology and microstructure of the materials were observed using field emission scanning electron microscopy (FESEM, Hitachi S-4800) and transmission electron microscopy (TEM, JEOL-2100). The elemental composition and the valence state of the elements were measured by X-ray photoelectron spectroscopy (XPS, Thermo ESCALAB250XI). The light absorption properties of the synthesized samples were characterized by ultraviolet-visible diffuse reflectance spectroscopy (UV-vis DRS, ShimadzuUV-2600). The charge transfer properties of the photocatalyst were studied using photoluminescence (PL, Shimadzu RF-6000) spectroscopy. ESR spectra were obtained using a JEOL JES-FA200 EPR spectrometer. In the electrochemical system of a three-electrode quartz cell, 0.5M Na2SO4 was used as the electrolyte, and the Mott-Schottky curve was measured. A Pt electrode was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode. 5 mg of the photocatalyst sample was dispersed in 1 mL of ethanol and 20 μL of Nafion solution to prepare a mixed solution, which was then applied on a FTO conductive glass sheet as a working electrode.

[0070] 1.4 Photocatalytic degradation

[0071] Typically, the photocatalytic degradation of LEV is studied by simulating sunlight at room temperature using a 300W xenon lamp. For a typical photocatalytic experiment, 40 mg of the prepared photocatalyst was added to 50 mL of LEV solution (15 mg / L, solvent was deionized water). After the suspensions were ultrasonically treated for 10 min, they were stirred in a dark environment for 20 min to reach adsorption-desorption equilibrium. Then, the photocatalytic degradation was carried out by turning on the light source for 3 h, and 3 mL of the suspension was extracted and passed through a 0.45 μm filter membrane at a time interval of 30 min. The absorbance of LEV was measured at 288 nm using a UV-visible spectrophotometer. In addition to the concentration decay, the final percentage removal efficiency (RE) was also used to evaluate the degradation performance:

[0072] RE=[(C0–C) / C0]×100% (1)

[0073] Where C0 is the initial LEV concentration and C is the LEV concentration after degradation. In order to find the active species produced by MCN / BWO (1:1), 1.0 mmol L -1 Isopropyl alcohol (IPA), EDTA and ascorbic acid (VC) were used as quenchers to quench hydroxyl radicals (OH), holes (h + ) and superoxide anion radicals (·O2 - ) are quenched. The free radicals ·OH and ·O are quenched by electron spin resonance (ESR). 2-Further identification was carried out.

[0074] 1.5 Isolation and identification of degradation intermediates

[0075] The photocatalytic performance of the prepared materials was evaluated by degrading LEV (15 mg / L) under simulated sunlight, and the degradation intermediates were identified. The detailed operation procedure is as follows. The LEV concentration was determined using LC-MS. Specific liquid phase conditions, chromatogram: (LC-MS, AB SCIEX Triple Tof5600), column: waters C18 column, 1.7μm, 2.1mm×100mm, column temperature: 35℃, injection volume: 10.0μL, flow rate: 0.2mL / min, mobile phase: A: 0.1% formic acid water; B: acetonitrile. AnalystLauncher software was used for the identification of LEV intermediates. Gradient elution method was used: 0-15min, V(A):V(B)=95:5. 15-18 minutes, V(A):V(B)=0:100. 18-20 minutes, V(A):V(B)=95:5. Ion source: HESI, auxiliary gas rate: 35mL / min, spray voltage: positive ion 5.5Kv, capillary temperature: 550℃.

[0076] 2 Results and discussion

[0077] 2.1 Structural characterization

[0078] The phase composition and crystal structure of MCN, BWO and MCN / BWO with different molar ratios were characterized by XRD, such as Figure 1 As shown in (a). The XRD spectrum of MCN shows two diffraction peaks, one is a typical diffraction peak at about 27.3° corresponding to the (002) plane of g-C3N4, which can be attributed to the interlayer stacking reflection of the conjugated aromatic system. The other is a weak peak at about 13°, which can be attributed to the (100) reflection of g-C3N4 of the in-plane structural motif. The XRD spectra of BWO and MCN / BWO with different molar ratios are at 28.30 ° ,32.91 ° ,47.14 ° ,55.99 ° ,58.54 ° ,69.04 ° ,76.08 ° , and 78.53 °There are obvious diffraction peaks at 27.4°, corresponding to the (131), (002), (202), (133), (262), (083), (2102) and (204) planes of the orthorhombic system of BWO (JCPDSNO.39-0256). The characteristic peaks in the XRD spectrum indicate that the prepared BWO is a pure andalusite phase. It must also be mentioned that no obvious MCN diffraction peaks appear in the XRD spectrum of MCN / BWO, which is due to the low crystallinity of MCN and is attributed to the characteristic peaks of MCN and BWO at 27.4°. ° MCN / BWO has a similar diffraction pattern to BWO, indicating that the introduction of MCN has no effect on the crystal structure of BWO. In addition, no impurity peaks were identified in all synthesized photocatalysts, confirming that no impurities were present during the entire synthesis process. Figure 1 As shown in (b), the wavelengths of pure MCN, pure BWO, and MCN / BWO were analyzed at 500-4000cm -1 FT-IR spectrum. At about 807cm -1 The peak at 1200-1750cm -1 The peaks in the absorption bands in the range belong to the vibrational stretching modes of aromatic CN and C=N bonds. -1 The broad peak at 500-800 cm-1 is attributed to the stretching and deformation modes of the uncondensed -NH2 groups. -1 The main peaks are shown at 1241, 1321, 1410, 1572 and 1642 cm -1 The characteristic peaks at are related to the stretching vibration mode of CN or C=N heterocycle. Obviously, the spectrum of the composite (MCN / BWO) covers all the characteristic peaks of MCN and BWO. The coexistence of the characteristic peaks of MCN and BWO in the spectrum of MCN / BWO indicates that there is no structural change in MCN / BWO during the hydrothermal process and the assembly is successful.

[0079] The SEM, TEM, HRTEM, elemental spectra, and EDS results of the samples are shown in Figure 2 In. Pure MCN has an irregular layered structure with uneven size distribution and many voids inside. After thermal exfoliation modification, MCN is in the form of nanosheets. Pure BWO has a compact flower-like structure. When MCN nanosheets are added to BWO, the BWO sheets are dispersed and anchored to the MCN substrate. SEM of MCN / BWO with different molar ratios (1:1, 3:1, 1:3) was characterized, and the results are shown in Figure 2As shown in (d)-(f). The morphology of MCN / BWO (3:1) is irregular and dense, which may be caused by a large amount of MCN. MCN / BWO (1:1) has a uniform stacking structure, in which BWO nanoparticles are tightly anchored on the MCN substrate. For MCN / BWO (1:1, 3:1 and 1:3) composites, SEM images show the presence of a large number of BWO spherical structures, or a large number of MCN nanosheets, indicating successful composite. According to the above analysis, there is an optimal content ratio of MCN / BWO composites, and the MCN / BWO (1:1) composite is more successfully composited, showing a more regular morphology and a more uniform distribution. The TEM image of the MCN / BWO (1:1) composite also clearly shows BWO and MCN nanosheets. In the high-resolution transmission electron microscopy of MCN / BWO (1:1), the (241) crystal plane of BWO and the (002) crystal plane of MCN produced lattice fringes of approximately 0.174nm and 0.336nm, respectively. In addition, from Figure 2 In (k), it can be seen that the BWO nanosheets with obvious lattice fringes are surrounded by MCN nanosheets, which is the most direct and effective evidence of the formation of heterojunction. This strong surface connection between BWO and MCN can confirm the construction of the heterojunction, and it can also provide a favorable pathway for charge carrier transport in the reaction. The results show that the MCN / BWO composite material was successfully prepared. In addition, the mapping image and EDS ( Figure 2 The percentages in (g1)–(h) show that Bi, W, O, C, and N elements are uniformly dispersed on the MCN / BWO heterojunction, which further proves the successful synthesis of the composite.

[0080] Exploration of the surface chemical composition and elemental chemical states of MCN, BWO, and MCN / BWO (1:1) by high-resolution XPS spectroscopy revealed important insights. All data were calibrated based on the Cl binding energy of 284.8 eV. Figure 3 The XPS spectrum in (a) shows that C, N, Bi, W and O elements coexist in the MCN / BWO composite, which is consistent with the EDS results. Figure 3 The C1s signal in (b) contains three different peaks at 288.36, 286.19, and 284.8 eV, which belong to the sp 2 Hybridized C (N=CN), sp of graphite site 3 Hybridized C-(N)3 and sp 2 Hybridized CC bond. The N 1s spectrum shows four peaks at 404.61, 401.61, 400.40 and 398.83 eV ( Figure 3 In (c), they are respectively attributed to the π excitation in the triazine ring, the amino group with hydrogen atoms (CNH), the tertiary nitrogen N-(C)3 group and the sp2 - Hybrid N (CNC). Figure 3 As shown in (f), the two peaks at 531.55 eV and 530.19 eV in the O1s spectrum of MCN / BWO are related to WO and Bi-O bonds. The Bi 4f spectrum of BWO shows two peaks at 164.51 eV (Bi4f5 / 2) and 159.21 eV (Bi 4f7 / 2), which indicates that Bi is present in MCN / BWO (1:1) as Bi 3+ The W 4f spectrum of BWO can be fitted by two peaks at 37.52 eV (W 4f5 / 2) and 35.39 eV (W 4f7 / 2), corresponding to W 6+ . It is worth noting that the above-mentioned N-(C)3 and C-(N)3 groups verify the tris-triazine structure of MCN, thereby confirming the presence of MCN in the MCN / BWO heterojunction. In addition, compared with pure MCN, it is worth noting that the C1s and N1s peaks in MCN / BWO shift to higher binding energies, demonstrating the close contact of BWO and MCN. In contrast, the peaks of Bi 4f, W 4f and O1s shift to lower binding energies than those in BWO, demonstrating the existence of certain electronic interactions between MCN and BWO. This shift further demonstrates the strong electron migration of the interaction between MCN and BWO. XPS analysis further confirms the successful construction of the MCN / BWO heterojunction, rather than a simple physical mixing.

[0081] 2.2 Photoelectrochemical measurements

[0082] The present invention uses ultraviolet-visible diffuse reflectance spectroscopy (UV-vis DRS) to study the optical properties of all samples. Figure 4 In (a), as MCN is loaded onto BWO, the UV absorption edge of MCN / BWO undergoes a significant red shift, indicating that the construction of the composite catalyst can promote the absorption of visible light, thereby forming more active substances for effective photocatalytic activity. Figure 4 In (b), the band gap (Eg) of these materials can be estimated by the following equation.

[0083] (αhν) 1 / n =A(hν-Eg) (2)

[0084] The absorption coefficient, Planck constant, optical frequency (Hz), constant, and band gap energy are represented by α, h, v, A, and Eg, respectively, while n is determined by the type of optical transition in the material. For direct band gap semiconductors, n is 1 / 2, and for indirect band gap semiconductors, n is 2. Since MCN is a direct transition semiconductor and BWO is an indirect transition semiconductor, the n values ​​for MCN and BWO are 1 / 2 and 2, respectively. By plotting (αhv) 2 and (αhv)1 / 2 The curve of E relative to hv is obtained g The estimated Eg values ​​of MCN and BWO are 2.78eV and 2.67eV, respectively. Figure 4 In addition, in order to determine the CB and VB edge positions of MCN, BWO, MCN / BWO (1:1), MCN / BWO (3:1) and MCN / BWO (1:3), the flat band potential (E fb ) and pn-type characteristics were measured. All prepared photocatalysts showed a positive slope, such as Figure 4 As shown in (c), these samples are n-type semiconductors and electrons are the majority of charge carriers. fb The values ​​were determined by determining the intersection of the potential values ​​with the horizontal axis, yielding -0.66 eV, -0.59 eV, -0.55 eV, -0.62 eV, and -0.47 eV (vs. Ag / AgCl), respectively. NHE =E Ag / AgCl +0.197, E of MCN, BWO, MCN / BWO(1:1), MCN / BWO(3:1) and MCN / BWO(1:3) fb = -0.46eV, -0.39eV, -0.35eV, -0.42eV and -0.27eV (relative to NHE) respectively. Since the Fermi level of a semiconductor is approximately equal to its flat band potential, the Fermi level of different materials can be evaluated by measuring their flat band potential. It is generally believed that the E of an n-type semiconductor is fb Potential ratio E CB Therefore, the E values ​​of the converted MCN, BWO, MCN / BWO (1:1), MCN / BWO (3:1) and MCN / BWO (1:3) are 0.2 eV higher. CB The values ​​were determined to be -0.66 eV, -0.59 eV, -0.55 eV, -0.62 eV and -0.47 eV, respectively. VB =E CB +E g , E of MCN, BWO VB The values ​​are 2.12 eV and 2.08 eV (vs. NHE), which are closely matched with the previously calculated VB values. Meanwhile, the VB-XPS spectra of MCN and BWO are used to further verify the obtained E VB Value. Figure 4 As shown in (d), the E VBThe values ​​were determined to be 2.22eV and 2.30eV, which are very similar to the above calculated values. The separation behavior of photogenerated carriers in the synthesized photocatalyst was studied by analyzing the photoluminescence emission spectrum (PL) at an excitation wavelength of 350nm. For photocatalytic materials, the higher the PL intensity, the higher the electron-hole recombination rate and the weaker the photocatalytic performance. Figure 4 As shown in (e), the original MCN has a strong emission peak, which can be attributed to the recombination of photogenerated electrons and holes in MCN. In addition, compared with MCN, the MCN / BWO binary photocatalysts exhibit relatively weak photoluminescence signals, among which MCN / BWO (1:3) is the weakest among all prepared binary photocatalysts. The PL emission intensity of BWO is almost negligible.

[0085] To further evaluate the photocatalytic activities of various prepared samples, transient photocurrent (TPC) and electrochemical impedance spectroscopy (EIS) analyses were performed. Figure 4 (g) shows the photocurrent response of MCN, BWO and binary heterojunction photocatalyst MCN / BWO under simulated sunlight. Compared with MCN and BWO, the MCN / BWO composite material exhibits a stronger photocurrent intensity, indicating that the MCN / BWO photocatalyst has better electron-hole pair separation efficiency and longer photogenerated carrier lifetime. In addition, relevant studies have shown that the smaller the Nyquist curve radius, the faster the charge transfer and the stronger the photocatalytic activity. Figure 4 As shown in (f), the Nyquist curve radius of MCN / BWO is smaller than that of pure MCN and BWO, indicating that its charge separation efficiency is faster and therefore more favorable. In addition, the SPV amplitude as a function of the incident wavelength reveals the photoactive spectral range and separation efficiency of the photogenerated charges in the semiconductor material. Generally, a stronger SPV response indicates a higher separation efficiency of the photoexcited charges. Figure 4 (h) shows the SPV amplitude spectrum of the MCN / BWO (1:1) composite. It is found that the SPV response of the MCN / BWO (1:1) composite is greatly increased, indicating that the formation of MCN / BWO is conducive to the separation of photogenerated carriers. Overall, these findings emphasize the remarkable photocatalytic performance exhibited by the binary heterojunction photocatalyst MCN / BWO.

[0086] 2.3 Photocatalytic degradation performance

[0087] 2.3.1 Photocatalytic activity of LEV on different catalysts

[0088] The photocatalytic degradation of LEV was carried out under simulated sunlight to evaluate the photocatalytic activity, such as Figure 5As shown in (a), all catalysts have photocatalytic effects on LEV degradation. Under simulated sunlight, the removal rates of LEV by MCN, BWO, MCN / BWO (1:3), MCN / BWO (1:1) and MCN / BWO (3:1) systems were 77.67%, 96.16%, 95.07%, 98.14% and 93.98%, respectively. With the extension of irradiation time, the absorbance decreased significantly. From the degradation results, the activity of the MCN / BWO (1:1) composite catalyst is better than that of other catalysts, which is due to the full contact and close combination of BWO and MCN, as shown in Figure 2. Figure 2 As shown in (d). In addition, Figure 5 (b) shows the photodegradation efficiency of LEV by MCN / BWO (1:1) photocatalyst under different illumination. Under simulated sunlight, visible light and sunlight, the LEV degradation rates are 98.14%, 87.41% and 95.94%, respectively. Taking all factors into consideration, the present invention takes MCN / BWO (1:1) binary heterojunction photocatalyst as the main research object.

[0089] In addition, the photocatalytic activities of different photocatalysts were further quantitatively evaluated using the pseudo-first-order reaction kinetic model (Eq. (3)):

[0090] ln(C0 / C t )=kt (3)

[0091] Where C0 and C t is the LEV concentration at 0 min and t min of the photo-Fenton reaction time, and k is the proposed first-order kinetic apparent rate constant. According to equation (3), Figure 5 The slope of the fitting line in (c) is the chemical reaction rate constant k. The results show that MCN / BWO (1:1) has excellent photocatalytic performance, and the k value is 44.3×10 -3 min -1 , which are 2.58 times, 1.18 times, 1.42 times and 2.36 times of blank, MCN, BWO, MCN / BWO (1:3), and MCN / BWO (3:1), respectively. In order to further demonstrate the stability and recyclability of the MCN / BWO (1:1) heterojunction photocatalyst, continuous degradation cycles of LEV were carried out under sunlight irradiation. The specific procedure of the recycling experiment is as follows: a series of three experiments were carried out under the same conditions. After one cycle, the MCN / BWO (1:1) photocatalyst was collected by centrifugation, washed 6 times with deionized water and anhydrous ethanol, and then dried at 60 °C to obtain MCN / BWO after one cycle. The cycle was repeated three times to explore the recyclability of MCN / BWO. The results are shown in Figure 6As shown in (a), the removal efficiency experienced a slight decrease throughout the three cycles, from 97.48% in the initial cycle to 92.58% in the last cycle, which indicates a minimal decrease in the photocatalytic degradation efficiency. The decrease in the photocatalytic performance of MCN / BWO (1:1) is mainly attributed to the exhaustion of the photocatalyst and the occupation and reduction of the active sites. At the same time, the XRD analysis of MCN / BWO (1:1) showed no discernible changes after three experimental cycles (e.g. Figure 6 The results show that the crystal structure of the MCN / BWO (1:1) type heterojunction photocatalytic material remains intact after use, indicating that the MCN / BWO (1:1) type heterojunction photocatalytic material is very stable under visible light irradiation. The above research results show that the MCN / BWO (1:1) heterojunction photocatalyst shows excellent reusability and robustness, making it a promising photocatalyst with practical value for eliminating organic pollutants. Therefore, the type II heterojunction MCN / BWO photocatalytic material is a new type of material with high stability, high efficiency and recyclability that can be used to degrade LEV, making it a very promising candidate for wastewater treatment applications compared to other photocatalysts listed in Table 1.

[0092] Table 1 Comparison of levofloxacin degradation by different photocatalysts

[0093]

[0094] 2.4 Photocatalytic mechanism

[0095] 2.4.1 Detection of active substances

[0096] like Figure 7 As shown in (a), IPA, EDTA and VC are used to capture OH, h + and O2 - The results showed that the addition of EDTA and VC decreased the photocatalytic removal efficiency of MCN / BWO from 94.36% to 45.81% and 37.12%, respectively. + and O2 - It makes an important contribution to the photocatalytic reaction of MCN / BWO. IPA has a slight effect on the removal of LEV, indicating that ·OH plays a small role in the photocatalytic process. In addition, to further test the existence of free radicals, we performed ESR tests under dark conditions and under illumination. Figure 7 As shown in (c)-(d), no obvious ·O2 - and ·OH signals, indicating that MCN / BWO (1:1) does not produce and ·O2 under dark conditions - and ·OH. In contrast, under light exposure, the corresponding -The unique and robust characteristic peaks of DMPO-·OH adducts are easily discernible, indicating that MCN / BWO produces ·O2 - and ·OH, which can degrade LEV under simulated sunlight. It is obvious that the strong oxidizing property of ·OH is inconsistent with its secondary role in the photocatalytic process. This indicates that h + Prefers to react with pollutants rather than oxidizing H2O or OH - Formation of ·OH.

[0097] 2.4.2 Possible photocatalytic mechanism

[0098] Based on the experimental results, a possible photocatalytic mechanism for LEV degradation was proposed. Fig.12 As shown, when sufficient visible light is irradiated on the BWO and MCN semiconductors, the electrons in the VB can be excited to generate electron-hole pairs, and then the electrons jump to the CB and leave a corresponding number of holes in the VB (Equations (4)-(5)). Since the CB potential of MCN (-0.66 eV) is more negative than the CB potential of BWO (-0.59 eV), the electrons in the CB of MCN are easily transferred to the CB of BWO. On the contrary, since the VB potential of BWO (2.30 eV) is more positive than the VB potential of MCN (2.22 eV), the holes in the VB of BWO are more easily transferred to the VB of MCN. Therefore, electrons gather in the CB of BWO, while holes gather in the VB of MCN, achieving charge separation. Compared with O2 / ·O2 - Compared with the redox potential of NHE (-0.32 eV vs NHE), the CB potential of BWO is more negative, resulting in the - Reduction of dissolved O2 to produce O2 - Free radicals, and then degrade LEV into CO2, water and small molecules (Eqs. (6)-(7)). At the same time, since the oxidation potential of the holes in the VB of MCN is weak (2.22 eV), the potential of VB is lower than the redox potential of ·OH / H2O (+2.68 eV vs NHE), and the holes on MCN cannot directly oxidize the adsorbed H2O to generate ·OH. These results are consistent with Figure 7 The conclusions of the active substance capture experiment are inconsistent with the ESR results. + Preferentially reacts with pollutants rather than oxidizing H2O or OH - ·OH is formed (Equation (8)), while the highly oxidizing species ·OH is generated due to the reduction of oxygen (Equations (9)-(10)). Therefore, the prepared type II heterojunction material promotes the effective separation and transfer of photogenerated carriers. A schematic diagram illustrating this mechanism is shown in Fig.12 Given in.

[0099] MCN+hv→e - CB(MCN)+h + VB(MCN) (4)

[0100] BWO+hv→e - CB(BWO) +h + VB(BWO) (5)

[0101] e - CB(BWO) +O2 → ·O2 - (6)

[0102] O2 - +LEV→CO2+H2O+small molecules (7)

[0103] h + VB(MCN) +LEV→CO2+H2O+small molecules (8)

[0104] 2e - +O2+2H + →H2O2 (9)

[0105] H2O2+·O2 - → OH+OH - +O2 (10)

[0106] 2.4.3 Possible degradation products and pathways

[0107] To further elucidate the photocatalytic degradation of LEV on MCN / BWO (1:1), 3D EEMs were used to monitor the fluorescence changes during the entire reaction process. Figure 8 As shown in Figure 2, different fluorescence signals were clearly present in the initial LEV solution. x / E m The two peaks at (400-600nm) / (200-400nm) are attributed to humic acid chemicals. x / E m The fluorescence at (400-600nm) / (200-400nm) indicates the presence of LEV, and the peak begins to weaken during the adsorption stage, which is attributed to the addition of the catalyst, which has a certain adsorption capacity ( Figure 8 After the system was exposed to sunlight for 30 minutes ( Figure 8 In (c), the fluorescence peak of LEV weakened after 30 min of photoreaction, indicating that some LEV was photocatalytically degraded. Figure 8In (d), due to the strong photocatalytic performance of the MCN / BWO binary photocatalyst, the continuous mineralization of LEV and its degradation intermediates caused the humic acid fluorescence area to gradually decrease. Compared with the fluorescence signal of the initial LEV solution, the fluorescence signal of the humic acid solution decreased significantly in the E x / E m The peak at (400-600nm) / (200-400nm) was particularly obvious. Subsequently, as the reaction time increased, the intensity of the two fluorescence signal peaks gradually decreased, indicating further degradation of LEV. Finally, after 90 minutes of irradiation ( Figure 8 In (f), E x / E m The fluorescence signal centered at (400-600nm) / (200-400nm) completely disappeared. As the reaction proceeded, the fluorescence intensity continued to weaken, indicating that LEV was effectively degraded, indicating that humic acid compounds were completely degraded and transformed during the degradation process, and finally mineralized into CO2, H2O and lower molecular weight intermediates. This observation is consistent with the results of earlier LEV photodegradation experiments, further confirming the significant photocatalytic degradation ability exhibited by the MCN / BWO binary heterojunction photocatalyst.

[0108] By LC-MS technology, in positive ion mode, the possible degradation intermediates and pathways of LEV under simulated sunlight were analyzed. Fig. 9 As shown (Table 2 shows the degradation intermediates). The initial substrate LEV (m / z 362) and the entire degradation process mainly occur on the quinolone and piperazine groups. Route I: LEV is dealkylated to P1 (m / z = 396). C6 and C7 of P1 are attacked to form P2 (m / z = 336). Afterwards, LEV decomposes into small molecules (P3 (m / z = 218)). Route II: LEV can be decomposed to form P4 (m / z = 318) through hydroxylation and deacetylation processes. P5 (m / z = 230) is obtained by the cleavage of the piperazine ring and N-demethylation reaction. It is then reacted with ·O2 -,·OH oxidation, resulting in unstable small molecule intermediates, including P6 (m / z = 175). Route II: LEV is initially oxidized and decarboxylated to form P7 (m / z = 318), which can be converted to P9 (m / z = 290) on the one hand by opening of the piperazine ring, and to P8 (m / z = 271) on the other hand by demethylation and deacetylation. Further deacetylation of P7 leads to the formation of P10 (m / z = 300). Route IV: The first pathway is LEV minus hydrogen to obtain product P11 (m / z 360), which is then further oxidized to obtain product P12 (m / z = 334). In addition, product P12 further participates in the fifth degradation pathway. Route V: The product P13 (m / z = 279) is formed by removing the piperazine group from the parent ion, and then the product P14 (m / z = 167) is obtained by removing the C6H7FN group. Finally, H2O, CO2 and other small molecules are generated. The results of LC-MS analysis showed that MCN / BWO could decompose LEV into small molecular products, gradually remove various functional groups, and further oxidize to CO2 and H2O.

[0109] 2.4.4 Ecotoxicity analysis of LEV and degradation intermediates

[0110] The intermediates produced during the degradation of organic pollutants are potentially harmful to the environment. Therefore, it is necessary to estimate the toxicity of these intermediates and compare them with the toxicity of the original pollutants. Using the toxicity evaluation software TEST, quantitative structure-activity relationship (QSAR) was used to evaluate the toxicity of LEV and its intermediates to important toxicity indicators such as Daphnia magna, Fatheadminnow, rat oral LD50, developmental toxicity, mutagenicity and bioaccumulation factor. The results are as follows Fig.10 shown. Fig.10 (a) is the LC of Daphnia magna corresponding to LEV and its intermediates 50 -48h, the lower the value, the greater the toxicity. LEV corresponding to Daphnia magna LC 50 The LC values ​​of P5, P6, P7, P10, P12, and P13 are equivalent to the LEV values. 50 The values ​​are all higher than the main value of LEV, that is, the toxicity is lower than LEV. 50 -96 h (median lethal concentration) is used to indicate acute toxicity and represents the concentration of the chemical in water that will cause 50% of fathead minnows to die after 96 hours. 50 -96 h is the highest concentration of the chemical in water. Generally speaking, LC 50 The lower the -96h value, the higher the toxicity. Fig.10As shown in (b), LEV has acute toxicity, LC 50 -96h is relatively low, at 1.24 mg / L. In the early stage of degradation, the LC of LEV degradation products 50 -96h was lower, among which P2 was the lowest, at 1 mg / L, and had the greatest toxicity. As the degradation process progressed, the acute toxicity of the intermediates gradually decreased, among which the acute toxicity of P5 was much lower than LEV. These results show that the toxicity of LEV intermediates to fathead minnows was significantly reduced, and the catalytic reaction had a universal effect on reducing the toxicity of fathead minnows. Fig.10 As shown in (c), the mutagenicity of intermediates P5, P7, and P11 is unpredictable. Except for intermediates P2, P6, P11, P14, P7, P1, and P12, all LEV intermediates have oral LD50 values ​​in mice (LD 50 ), indicating that P2, P6, P11, P14, P7, P12, P13, P14, P15, P16, P17, P18, P19, P1 and P12 have lower toxicity, while the remaining intermediates have higher toxicity. Fig.10 As shown in (d), LEV is mutagenic, with a mutagenicity value of 0.65. P3, P8, P9, P11, P12, and P14 are positive for mutagenicity, and the mutagenicity of the remaining intermediates is lower than that of LEV. Fig.10 In (e), except for P12, P2, and P11, the developmental toxicity of all identified intermediates was lower than the original LEV. In particular, the developmental toxicity values ​​of the final intermediates (P5, P6, P9, P8, P14, P1, and P3) were significantly lower than the LEV. Fig.10 (f) is the evaluation value of the bioaccumulation factor. The evaluation value of the bioaccumulation factor of LEV is 3.53, P14 cannot be predicted, and the evaluation values ​​of P1, P2, P5, P9, P11 and P13 are all lower than LEV, indicating that the possibility of accumulation of these intermediates in the body is lower than LEV. In particular, P1 (1.09) and P5 (0.84) are extremely unlikely to accumulate in the body. The results show that the MCN / BWO system can not only efficiently degrade LEV, but also significantly reduce its toxicity to the environment.

[0111] Table 2. Possible molecular formulas, m / z values ​​and structures of LEV and its intermediates

[0112]

[0113]

[0114] 3 Conclusion

[0115] The MCN / BWO photocatalyst prepared by hydrothermal method can effectively degrade low concentration of LEV in water. The physicochemical properties of the samples were studied using XRD, FTIR, XPS, SEM, TEM and SEM. These results confirmed the successful synthesis of MCN / BWO. The results showed that the photocatalytic activity of the MCN / BWO (1:1) composite photocatalyst was better than that of MCN, BWO, MCN / BWO (1:3) and MCN / BWO (3:1) composite photocatalysts. Under the optimal reaction conditions, the degradation rate of LEV reached 98.14% after 180 min of illumination. In addition, the MCN / BWO catalyst has excellent stability and cyclic performance. The identification of the main active species in the LEV degradation process was based on free radical capture experiments, which showed that photogenerated holes (h + ) and superoxide radicals (·O2 - ) plays a key role. The formation of type II heterojunction was confirmed by HR-TEM, Mott-Schottky, XPS, VB-XPS, capture experiments and ESR results. Considering the optical properties of the binary complex, MCN and BWO have band gap energies of 2.78 and 2.67 eV, respectively. Through the analysis of fluorescence spectra, photocurrent response and electrochemical impedance, it is believed that MCN / BWO has a lower recombination rate and better electron-hole separation and transfer ability than pure MCN and BWO. The possible degradation pathways of LEV were speculated by LC-MS and 3D EEMs techniques, and the toxicity of LEV and its intermediates was evaluated by quantitative structure-activity relationship (QSAR) using the toxicity assessment software TEST, which provides a new idea for the environmental remediation of LEV wastewater and has potential practical application value.

[0116] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a type II heterojunction photocatalyst, characterized in that: The following steps are involved: The g-C3N4 nanosheets and tungsten source were dissolved in water and mixed to obtain solution A; Dissolve the bismuth source in glacial acetic acid to obtain solution B; Adding the solution B into the solution A to obtain a suspension C; The suspension C is subjected to a hydrothermal reaction to obtain the type II heterojunction photocatalyst.

2. The method for preparing type II heterojunction photocatalyst according to claim 1, characterized in that: The g-C3N4 nanosheets are made from melamine.

3. The method for preparing type II heterojunction photocatalyst according to claim 2, characterized in that: The preparation method of the g-C3N4 nanosheets comprises the following steps: After the first calcination of melamine, CN is obtained; The CN is calcined for a second time to obtain the g-C3N4 nanosheets.

4. The method for preparing type II heterojunction photocatalyst according to claim 3, characterized in that: The temperature of the first calcination is 550-600° C., and the time is 4-5 hours; the temperature of the second calcination is 500-550° C., and the time is 2-3 hours.

5. The method for preparing type II heterojunction photocatalyst according to claim 1, characterized in that: The molar ratio of the g-C3N4 nanosheets to the sodium tungstate and bismuth nitrate is (1-3):1:2; the tungsten source is sodium tungstate; and the bismuth source is bismuth nitrate.

6. The method for preparing type II heterojunction photocatalyst according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 160-180° C. and the time is 12-13 hours.

7. The method for preparing type II heterojunction photocatalyst according to claim 1, characterized in that: After the hydrothermal reaction is completed, the steps of collecting the product by centrifugation, washing and drying are also included.

8. A type II heterojunction photocatalyst prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the type II heterojunction photocatalyst as claimed in claim 8 in the photocatalytic degradation of fluoroquinolone drugs.

10. The use according to claim 9, characterized in that: The fluoroquinolone drug is levofloxacin.

Citation Information

Patent Citations

  • g-C3N4 modified self-doping Bi2WO6 composite photocatalyst and preparation method and application thereof

    CN105688970A

  • Preparation method of CdS / g-C3N4 composite photocatalyst material with Z-shaped heterojunction synthesized by hydrothermal method

    CN112427045A

  • Preparation method of high-photocatalysis phosphorus-doped graphite phase carbon nitride / bismuth tungstate heterojunction

    CN114130415A

  • Preparation method of g-C3N4 / Au / Bi2WO6 composite material

    CN116809109A

  • Visible light catalytic material and preparation method and application thereof

    EP3848122A1